2001
DOI: 10.1021/bi0019343
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentation Studies Reveal a Direct Role of Phosphorylation in Smad3:Smad4 Homo- and Hetero-Trimerization

Abstract: SMAD proteins are known to oligomerize and hetero-associate during their activation and translocation to the nucleus for transcriptional control. Analytical ultracentrifuge studies on Smad3 and Smad4 protein constructs are presented to clarify the model of homo- and hetero-oligomerization and the role of phosphorylation in the activation process. These constructs all exhibit a tendency to form disulfide cross-linked aggregates, primarily dimers, and a strong reducing agent, TCEP, was found to be required to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
3

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 33 publications
1
39
0
3
Order By: Relevance
“…8). This stoichiometry is consistent with the differential DNA sequence requirements for Smad3 and Smad4 binding to the PE2.1 element and the predominantly trimeric state of Smads in solution (52,53) as well as in the x-ray crystal structure of the MH2 domain (51). Complexes formed by Smad2 and Smad4 with either FAST-1 or FAST-3 at the Mix.2 promoter contain one FAST, two Smad2s, and one A, specificity of Smad4 binding to the PE2.1 oligonucleotide in the surface plasmon resonance assay.…”
Section: Effects Of Smad Interactions With Bhlhzip Proteins Onsupporting
confidence: 79%
“…8). This stoichiometry is consistent with the differential DNA sequence requirements for Smad3 and Smad4 binding to the PE2.1 element and the predominantly trimeric state of Smads in solution (52,53) as well as in the x-ray crystal structure of the MH2 domain (51). Complexes formed by Smad2 and Smad4 with either FAST-1 or FAST-3 at the Mix.2 promoter contain one FAST, two Smad2s, and one A, specificity of Smad4 binding to the PE2.1 oligonucleotide in the surface plasmon resonance assay.…”
Section: Effects Of Smad Interactions With Bhlhzip Proteins Onsupporting
confidence: 79%
“…For example, HO-1 induction was dependent on the presence of all three Smads (Figure 2), whereas other genes appeared to be selectively regulated by one Smad (Figures 2 and 4 and Table 1). Biochemical and crystallographic studies have shown that Smads can exist in a multitude of signaling complexes representing multiple oligomeric states that range from heterodimers to high molecular weight assemblies (Nakao et al, 1997;Jayaraman and Massague, 2000;Chacko et al, 2001;Correia et al, 2001;Wu et al, 2001;Qin et al, 2002). Still, the exact stoichiometry of Smad complexes remains controversial (Inman and Hill, 2002;Moustakas and Heldin, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Similar analyses with Smad3 indicate that endogenous Smad3 exists in multiple oligomeric states in unstimulated cells (8), while purified C-terminal fragments of Smad3 can be either monomeric or trimeric (11,12). Similarly, in the uninduced state, Smad4 can exist as monomers (7), dimers, or trimers (8), and crystallographic studies have shown that purified C-terminal fragments of Smad4 are trimers (13,14).…”
mentioning
confidence: 81%